Tathwir Mawad al-Taâ€™bir al-Tahriry â€˜Ala DhuÃ Maharat al-Tafkir al-Ãšlya li Tarqiyah Kitabah al-Maqalah li Thullabah Qism Taâ€™lim al-Lughah al-Ãrabiyyah - Tarmizi, Ahmad; Adam Ibrahim, Faisol Mahmud; Taufiqurrochman, R. (Arabiyatuna: Jurnal Bahasa Arab, 2022)
The process of developingÂ  learning material Â is very important in language education, and that learning materials should be adapted to the progress and demands of time.This paper aims to develop the material learning of arabic writing for Student of Department of Arabic Language University of Muhammadiyah Malang, this paper used Bolito and Julie model, and the data was collected through interview, observation, documents, questionnaire, and pre testÂ  and post test, the technique of data analysis using Miles, Huberman and Saldanaâ€™s theory, by condensing the data after collecting it, then displaying and summarizing it. The results for this search are; 1) Students need materials for writting essay in based on higher-order thinking skills. 2) the characteristics of material writting developed include (a) thematic and factual which suitable with the environment where the student live, for instance the move of the capital of Jakarta to borneo island in circumstances of new corona virus pandemic, and the phenomenon of street children and homeless people in Indonesia etc; Â (b) mind mapping to organize ideas; (c) Vocabulary. 3) The developed materials are valid for use Â due to it adapts to the condition where the students live and then help themÂ  gather the information before writing the article 4) Teaching materials for Arabic writting essay based on higher-order thinking skills are effective to improve studentsâ€™ ability in Arabic writing essays by solving problems from the topics, criticizing the subjetc which is encourage them to discuss and present their opinions Â by rewriting sentences and paragraphs in their language, and hence students practiced in three levels of higher order thinking skills: analytical, evaluative and creative thinking.Â